The Play of Gender Roles in Sheeba Shah’s Facing My Phantoms - Bista, Asmita (Prithvi Academic Journal, 2020)
Setting the novel in different time-periods (Rana regime, Panchayat System and Maoist movement), Sheeba Shah’s Facing my Phantoms has depicted the condition of Nepali males and is considered a historical document. This article aims to examine the factors that constrain the male characters to traditional and anti-traditional gender roles. It also studies the consequences faced by the characters while performing and defying gender stereotypes. To address this objective, Butler’s and Connell’s ideas have been used as they have claimed that masculinity and femininity like any other human attributes are fluid; in fact, it is constantly reconstructed in response to socio-political changes under the pressure of social norms. According to Butler, gender is something that is not a corporeal thing, but it is reproducing, changing, and moving. The significance of this article is to find insights in understanding the condition of males in the Nepali society. It concludes that the male characters of Shah’s novel oscillate between traditional and anti-traditional gender roles. Under the social pressure, they perform the roles of an assertive and authoritative father, aggressive and ruthless lover/husband, and rational and responsible son. Likewise, when they get influenced by socio-political changes, they fail to stick to stereotypical gender roles. Consequently, they appear in the emotional, docile, dependent, confused, and unassertive roles.